Examining the Growth of Sports Communication Programs in Higher Education Through a Questionnaire of Program Coordinators. (December 2019) - Hull, Kevin; Choi, Minhee; Kian, Edward (Ted) M.
As higher education institutions seek ways to attract, recruit, and retain students, some schools and colleges are creating sports communication or related programs. Using the student–customer model of higher education as a theoretical lens, this study questioned coordinators of those programs regarding their opinions of this quickly growing field. Results demonstrate that student interest, administrative and financial support, and having resources already in place before designing curricula are keys to building and sustaining successful sports communication academic programs. Results of this study can be used by schools looking to launch sports communication programs.